Exploring Thiophene Derivatives: Synthesis Strategies and Biological Significance - Mishra, Isha; Sharma, Vikram; Kumar, Nitin; Krishna, Gaurav; Sethi, Vandana Arora; Mittal, Ravi; Dhakad, Prashant K.; Mishra, Raghav (Medicinal Chemistry, 2025)
ObjectivesThiophene is one of the most important heterocyclic scaffolds with notable pharmacological properties. Thiophene and its derivatives are of particular interest among sulphur-containing heterocycles because of their similarities to numerous natural and synthetic compounds with identified potential. The purpose of this study is to extensively analyse the synthetic pathways adopted for synthesising thiophene derivatives and investigate their various biological functions.MethodsA comprehensive review of the existing literature was conducted to collect data pertaining to the methods that are employed for the synthesis of thiophene derivatives. A comprehensive search was carried out through relevant databases, including work published in 2024. A variety of synthesis procedures were identified and arranged, encompassing both traditional approaches like the Gewald reaction and contemporary ones like microwave-assisted synthesis and green synthesis. In addition, a comprehensive compilation of in vitro and in vivo studies was conducted to investigate the biological effects of 50 distinct thiophene derivatives. The primary focus of the studies was on various activities such as anti-cancer, anti-inflammatory, antiprotozoal, antibacterial, antioxidant, and antiviral functions.ResultsDiverse methodologies have been employed in the synthesis of thiophene derivatives, encompassing both conventional and modern methods. Furthermore, the biological potential of thiophene derivatives was investigated, demonstrating a broad range of actions. Key structural elements necessary for biological activity were clarified by investigations of the structure-activity relationship.ConclusionThe biological potential and flexible synthesis pathways of thiophene derivatives make them attractive candidates for use in medicinal and pharmaceutical chemistry. Understanding the different synthesis methods and biological actions of thiophene derivatives may assist rational design and create novel treatments for a variety of conditions. The potential for these compounds to be further explored and optimised is considerable for the next drug development initiatives.
Keywords: structure-activity relationship